Implementation of Hadith on Gender Towards Female Family Leaders in the PEKKA Group (Empowering Women Family Leaders) in Asahan District - Syam, Nur Fadhilah; Nurwandri, Andri (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2022)
Social life can not be separated from a leadership even to the realm of the family. Leaders in the household have been regulated by state regulations, namely KHI and Law no. 1 year 74 states that